Mechanical Properties of Lightweight Concrete Partition with a Core of Textile Waste - Kamran Aghaee; Mohammad Foroughi (Advances in Civil Engineering)
This investigation is focused on bending experiment of some prismatic perlite lightweight concrete. In these samples, textile waste fibers are confined with textile mesh glass fiber and embedded in the central part of cubic lightweight concrete specimens. Bending experiments revealed that lightweight concrete panels with a core of textile waste fiber have less density than water and high energy absorption and ductility. Furthermore, these composite panels by having appropriate thermal insulation characteristics could be used for partitioning in the buildings.